ВИМІРЮВАННЯ І ЗБІР ДАНИХ ПРО ПАРАМЕТРИ МАГНІТНИХ ПОЛІВ У ПРОГРАМНО-АПАРАТНОМУ КОМПЛЕКСІ ДЛЯ ЕКСПЕРИМЕНТАЛЬНИХ ДОСЛІДЖЕНЬ І НЕІНВАЗИВНОГО ДІАГНОСТУВАННЯ ЕЛЕКТРОЕНЕРГЕТИЧНОГО ОБЛАДНАННЯ - Мазманян, Р.O. (Інститут електродинаміки Національної академії наук України, 2025)
Diagnostics of power equipment, forecasting of the residual resource is an effective way to ensure its safe and long-term operation. Reduction of costs, reduction of diagnostic time are provided by non-invasive methods that do not require intervention in the design of the machine being diagnosed. The hardware and software complex is designed to study the relationship between changes in the patterns of magnetic field intensity distribution with faults in power equipment. In experimental studies with predetermined technical faults artificially introduced into the object, the complex will provide useful and reliable results, registering changes in magnetic field induction in the spatial, temporal and frequency domains of magnetic field physics. Selection and flexible configuration of data acquisition means will ensure the use of the most appropriate method of measurements, conversion and display of information about the studied faults. The article presents the main operating modes, graphical user interfaces of a personal computer and a mobile data acquisition system, which jointly perform the conversion, storage, analysis and display of measurement information obtained from various magnetic sensors. The generalized functional specification of the software of the complex, the design of the graphical user interface (GUI) as part of the real-time operating system (RTOS) will also be used in the development of problem-oriented systems for computer diagnostics of power equipment. Ref. 17, fig. 5.